IODINE AND SELENIUM BIOFORTIFICATION OF MICROGREENS (SPINACH) TO ALLEVIATE MINERAL NUTRIENT DEFICIENCY - ABBAS, T; ALTAF, K; TASADAQ, M; ANJUM, S; HUSSAIN, S; AHMAD, W; KHAN, AA; YOUNAS, HS (Biological and Clinical Sciences Research Journal, 2024)
Iodine (I) and Selenium (Se) are essential nutrients for the proper functioning of human and plant bodies. This study aimed to optimize the application method and dose/rate of nutrients for spinach biofortification to better serve human health and may prove more economical than adding these nutrients in supplements. The trial was conducted at the growth room, Department of Horticulture, University of Layyah, Layyah. Seed of spinach was procured from a certified agency and directly sown in the trays (2 inches deep). This study employed a total of three concentrations of two distinct nutrient treatments (I and Se) as well as a control, applied as basal and foliar spray methods. Each treatment was replicated thrice, each replication with a tray. The end product was analyzed for different attributes like morphological parameters, biochemical parameters (Total soluble solids, Vitamin C, acidity, carotenoids, chlorophyll contents, lipophilic antioxidant (LPA), starch contents, amino acids, carotenoids, flavonoids, and phenolic contents) and ionic contents (I and Se). Our results indicated that supplementation of I @ 2.5mg/L and Se @ 1mg/L concentration is optimal for maintaining the normal growth of plants and promoting the major I and Se concentration in the edible part of spinach. Thus, it could be proposed that the growth of spinach under I @ 2.5mg/L iodine can amount to 208µg and 238µg and Se ranged from 215.09µg and 186.51µg in shoots and roots, which can match the 150µg day-1 and 55 µg day-1 dietary iodine and selenium allowance recommended by WHO.